Ultrasound evaluation of peripheral nerves of the lower limb in diabetic peripheral neuropathy. Issue 145 (December 2021) - Goyal, Kanav; Aggarwal, Purnima; Gupta, Monica
Abstract: Purpose: Comparative evaluation of the cross-sectional area (CSA) of the sural and tibial nerves using ultrasound in diabetic peripheral neuropathy (DPN). Method: This study involved 210 participants divided into 3 groups: type 2 diabetics with DPN, type 2 diabetics without DPN, and controls. Ultrasound evaluation of the sural and tibial nerves was done using a 5–17 MHz linear transducer. The CSA of both the nerves was recorded in both lower limbs. Nerve conduction studies (NCS) were also done in all diabetic patients. Results: There were 70 participants in each group. All the three groups were gender-matched and no significant difference was observed between CSA values of the sural and tibial nerves between males and females and also in right and left lower limbs within a group. The sural nerve CSA was significantly higher in the DPN group than in diabetic patients without DPN and controls. The sensitivity of the sural nerve CSA was higher than the tibial nerve with a cut-off value of 4.41 mm 2 for CSA of the sural nerve. Conclusion: The sural nerve CSA at the superior border of lateral malleolus can be used for screening DPN. With well-established cut-off values may result in early initiation of the therapy even in NCS negative cases, thus reducing the morbidity associated with the disease. Ultrasound could be used as a first diagnostic tool for detection of DPN which can be followed by NCS in cases where ultrasound is non-diagnostic.